The role of coagulation hemostasis for development of early-onset preeclampsia in low-risk patients - M. G. Nikolaeva; K. V. Shchekleina; A. P. Momot; V. Yu. Terekhina; E. V. Grigorieva (Акушерство, гинекология и репродукция, 2022)
Aim: to determine a role of specific parameters of coagulation hemostasis for development of severe early-onset preeclampsia (еPE) in low-risk patients.Materials and Methods. A single-center prospective study included 40 patients with a physiological course of pregnancy and term delivery (control group) as well as 41 pregnant women with developed severe еPE (study group). Patients at the gestational age of 19–21 and 27–28 weeks in the comparison groups were examined for serum tissue factor (TF) activity; tissue factor pathway inhibitor (TFPI) and potential to generate thrombin in calibrated thrombography test.Results. Patients with developed ePE vs. control group were found to have significantly increased TF activity at both time points: 49.1 pmol/ml vs. 5.3 pmol/ml (p < 0.0001) and 56.7 pmol/ml vs. 6.6 pmol/ml (p < 0.0001); respectively. At gestational age of 19–21 weeks; patients in the study vs. control group had serum TFPI level significantly lower (1.1 U/ml vs. 1.6 U/ml; p < 0.0001) that was significant elevated up to 2.1 U/ml by 82 % at 27–28 weeks of pregnancy. At both time points; a significantly increased thrombin generation was detected in women with developed ePE.Conclusion. The development of ePE is characterized by increased potential to generate thrombin. TF has been identified as a more sensitive marker of activated coagulation hemostasis; and its significantly increased activity was recorded at gestational age of 19–21 weeks that allows us to consider TF as a prognostic biomarker.